Integration of ICT in the teaching profession in Nigeria - Nazeer Datti Abdullahi; Abdulmumin Ibrahim Abdulmumin (Aqlamuna: Journal of Educational Studies, 2024)
Information and Communication Technology (ICT) has revolutionized various aspects of life, including education. This paper examines the integration of ICT in the teaching profession in Nigeria. It begins by looking at the ICT in the teaching profession alongside the policy in relation to it in Nigerian context. It also explores the potential benefits of ICT for teachers, including enhanced lesson delivery, improved student engagement, and access to a wider range of learning materials. The paper also acknowledges the challenges faced by Nigerian teachers in ICT integration. Finally, it proposes recommendations for overcoming these challenges and maximizing the positive impact of ICT on Nigerian education. The recommendation among others include: the government and educational institutions should invest in expanding internet access, providing schools with adequate equipment, and ensuring proper maintenance Key words: Information Communication Technology, Teaching profession, Nigeria